Developmental genetics of the COPD lung. Issue 1 (December 2015) - Probert, Kelly; Miller, Suzanne; Kheirallah, Abdul; Hall, Ian
Abstract Chronic Obstructive Pulmonary Disease (COPD) is a debilitating disease of the lung which results in irreversible airflow obstruction and is currently the third leading cause of death worldwide. Genetic and environmental factors contributing to COPD are presently under investigation. As lung function measures cluster within families, we now know that lung function is partly inherited. Thus, identifying genes involved in determining lung function at the population level and in determining the risk of development of COPD is important. A thorough understanding of the mechanisms underlying maintenance of lung function and knowledge of how these are altered in lung disease could ultimately lead to targeted therapeutic approaches. This is of potential value in COPD because current treatments are designed to reduce symptoms but do not modify disease progression. Here, we review the genes identified from both meta-analyses of genome-wide association (GWA) studies of lung function in large populations and case control GWA studies in COPD. We hypothesise that mechanisms involved in the early development of the lungs may vary/alter and predispose to COPD later in life. We discuss the genes and pathways involved in normal lung development and ascertain whether they overlap with key genes identified from GWA studies. Epigenetic factors may also play an important role in lung function, development and disease. Furthermore, we discuss our findings on the functional characterisation ofHTR4 and genes within the 4q24 locus associated with both lung function and COPD. Lastly, we consider new genetic techniques and models to study candidate genes identified by the approaches discussed.